Correlation Between Hallux Valgus Severity and the Prevalence of Metatarsus Adductus in Hallux Valgus - Yuan‐Shao Chen; Che‐Han Liang; Han‐Ting Shih; Kao‐Chang Tu; Shih‐Chieh Tang; Shun‐Ping Wang (Journal of Foot and Ankle Research, 2025)
ABSTRACT Introduction Hallux valgus (HV) is a common foot deformity, with metatarsus adductus (MA) identified as a potential predisposing factor. MA has been shown to negatively affect surgical outcomes for HV, particularly in severe cases. This study aims to clarify the prevalence of MA in the HV population using different metatarsus adductus angle (MAA) measurement methods and assess whether MAAs are influenced by HV severity. Materials and Methods This retrospective study included 294 feet from 147 participants. Patients were classified into non‐HV (normal) and HV subgroups, with HV severity graded as mild, moderate, or severe based on the hallux valgus angle (HVA) measured on dorsoplantar weight‐bearing radiographs. The prevalence of MA was assessed using four radiographic measurements: Sgarlato's MAA (MAA4), modified Sgarlato's MAA (MAA5), modified Engel's angle, and the calcaneo‐second metatarsal angle (rearfoot‐MT2). The interclass correlation coefficient was used to evaluate the reliability of the measurements. The correlation between HVA and MAA was analyzed using Spearman's Rho coefficient, and the prevalence of MA was compared using various measures. Results After excluding 87 feet, 207 feet (146 HV and 61 non‐HV) from 147 participants were analyzed. All four MAA measurements showed excellent reliability, with the modified Engel's angle demonstrating the highest interobserver reliability and strongest correlation with HVA. HVA was significantly higher in the MA (+) group compared to the MA (−) group (32.21 vs. 24.78° and p = 0.001). The overall prevalence of MA in the cohort was 19.3% (MAA4), 24.2% (MAA5), 18.4% (modified Engel's angle), and 8.2% (rearfoot‐MT2). MA was significantly more prevalent in the HV group compared to the normal group (24.0% vs. 4.9%) when using the modified Engel's angle, with MA prevalence increasing as HV severity worsened. Conclusions MA is common among patients with HV, with its prevalence increasing in parallel with HV severity. The modified Engel's angle is a reliable and sensitive method for detecting MA associated with HV, particularly in severe cases, and its use can help tailor surgical plans to improve outcomes. Surgeons should be mindful of the presence of concomitant MA when planning HV surgery, as it may negatively affect surgical outcomes and increase the risk of recurrence.